The Role of Legislation, Regulatory Initiatives and Guidelines on the Control of Plastic Pollution - da Costa, João Pinto; Mouneyrac, Catherine; Costa, Mónica; Duarte, Armando C.; Rocha-Santos, Teresa (Frontiers in Environmental Science, 2020)
There has been an exponential interest in the occurrence and potential ecotoxicological consequences stemming from the growing prevalence of (micro)plastics in the environment. This has been especially evident by the increasing concern regarding the visible effects on marine ecosystems, with multiple local, regional and trans-national initiatives developed towards the mitigation of what has been construed as an environmental disaster. However, it is not clear what the benefits – if any – of the multitude of norms, regulations, laws and recommendations that have been proposed and/or implemented in recent years are. Furthermore, many of the proposed laws may be of limited applicability, particularly considering the extent to which plastic occurs in everyday life. Herein, the current regulatory instruments are overviewed, focusing on the existing proposals and the extent to which these are based on the currently available scientific data, as well as the foreseen challenges that may restrain the relevancy and suitability of such legislative proposals.